Romani sodobnih slovenskih pisateljic - Borovnik, Silvija (Slavistična revija, 2003)
The article discusses the forms of novels that have in recent times been penned by Slovene women writers and some publicists, such as Brina Švigelj (Brina Svit), Manca Košir, Erica Johnson Debeljak, Vesna Milek, Sonja Porle, and Nina Kokelj. The central part of the article includes tha analysis of the narative material published fron the beginning of the 1980s on. This materials illuminated in terms of its typological features and the relationship between the traditional and new narrative processes.
Keywords: Johnson Debeljak, Erica; Kokelj, Nina, 1972-; Košir, Manca, 1948-; Milek, Vesna; novel; Porle, Sonja, 1960-; roman; Slovene literature; slovenska književnost; slovenske pisateljice; slovenski roman; Švigelj Mérat, Brina, 1954-